Processable dispersions of photocatalytically active nanosheets derived from titanium diboride: self assembly into hydrogels and paper-like macrostructures. Issue 32 (12th August 2020) - James, Asha Liza; Lenka, Manis; Pandey, Nidhi; Ojha, Abhijeet; Kumar, Ashish; Saraswat, Rohit; Thareja, Prachi; Krishnan, Venkata; Jasuja, Kabeer
Abstract : An aqueous peroxo-route to synthesize processable dispersions of nanosheets from titanium diboride in high yields and their assembly into hydrogels and freestanding paper-like macrostructures. Abstract : Titanium diboride (TiB2 ), a layered ceramic material, is well-known for its ultrahigh strength, wear resistance, and chemical inertness. In this work, we present a simple one-pot chemical approach that yields sheet-like nanostructures from TiB2 . We serendipitously found that TiB2 crystals can undergo complete dissolution in a mild aqueous solution of H2 O2 under ambient conditions. This unexpected dissolution of TiB2 is followed by non-classical recrystallization that results in nanostructures with sheet-like morphology exhibiting Ti–O and B–O functional groups. We show that this pathway can be used to obtain an aqueous dispersion of nanosheets with concentrations ≥3 mg mL −1 . Interestingly, these nanosheets tend to transform into a hydrogel without the need of any additives. We found that the degree of gelation depends on the ratio of TiB2 to H2 O2, which can be tuned to achieve gels with a shear modulus of 0.35 kPa. We also show this aqueous dispersion of nanosheets is processable and forms hierarchical paper-like macrostructures upon vacuum filtration. Such an ability to assemble into free-standing 3D structures would enable a leap to practical applications. We also show that the high surface area and presence of oxy-functional groups on these nanosheets endow them a superior photocatalytic activity to degrade organic pollutants. This exemplifies the rich potential that TiB2 offers upon nanoscaling. The results presented here not only add a novel material to the 2D flatland but also urge the scientific community to revisit the chemistry of metal borides, that have been traditionally considered as relatively inert ceramics.